1999
DOI: 10.1016/s0954-6111(99)90153-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory function of healthy, urban, non smoking, Pakistani young adults aged 18–24 years

Abstract: Age may have a different contribution to normal lung function values in those aged less than 25 years, as compared to older individuals. We report regression equations predicting ventilatory parameters in this age group, as none have been reported from Pakistan. The study was conducted on students of King Edward Medical College Lahore, Pakistan. Participants had never smoked and reported no respiratory symptoms. In addition to anthropometric data, forced expiratory volume in 1 sec (FEV1), forced vital capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Spirometry results give a clue about the level of morbidity and life expectancy. These results help the physician in making a decision regarding the nature of disease, its severity and probable response to medication 4-6. Spirometry just give an overview of general respiratory health in the same way as the recording of blood pressure reveals about the overall cardiovascular health 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirometry results give a clue about the level of morbidity and life expectancy. These results help the physician in making a decision regarding the nature of disease, its severity and probable response to medication 4-6. Spirometry just give an overview of general respiratory health in the same way as the recording of blood pressure reveals about the overall cardiovascular health 7.…”
Section: Introductionmentioning
confidence: 99%
“…Considering specifically south Asia, very few studies have been done to establish a normative spirometry range among children and adolescents by taking age and height as an independent variable 9,10. Among developing countries specially in Pakistan, insignificant number of studies have been done for adult population but none of them reported any of the normative spirometry values for the children and adolescents 6,11,12. Because of this physician are diagnosing the children and adolescents on the basis of Polgar reference values, in which height is an independent variable 13.…”
Section: Introductionmentioning
confidence: 99%
“…Η διαφορά αυτή εξηγείται εν μέρει από το διαφορετικό μήκος του κορμού σε σύγκριση με το ύψος των διάφορων φυλών καθώς επίσης και σε διαφορές στην ελεύθερη λίπους μάζα σώματος, στις διαστάσεις του θώρακα και στην ισχύ των αναπνευστικών μυών(34). Σύμφωνα με κάποιες άλλες μελέτες(111,112) διαφορές στο μέγεθος των κυψελίδων και στο μέγεθος των αεραγωγών σε διαφορετικές εθνότητες, μπορεί να είναι αιτίες που συμβάλουν στις διαφορετικές προβλεπόμενες τιμές. Λίγες εργασίες υπάρχουν σχετικά και η συγκριτική μελέτη των εργασιών αυτών δεν προσφέρει σημαντική βοήθεια, διότι αφορούν σε διαφορετικούς πληθυσμούς και έχουν γίνει με διαφορετική μεθοδολογία.…”
unclassified